Metabolic Improvements From CoQ10 and ALA in PCOS Patients - Hussein, Dhirgham Saif Aldean; Kadhim, Sinaa Abdul Amir; Swadi, Asma Abdul Jaleel (Indonesian Journal on Health Science and Medicine, 2025)
Background: As more women search for natural solutions or prescription medications to manage their symptoms, supplements like Alpha Lipoic Acid and CoQ10 are growing in popularity. Combining these with a personalized plan can lead to better health outcomes and a higher quality of life. Aim of the study: the aim of the current research project is to evaluate the effect of combined administration of metformin, ALA and CoQ10 on PCOS metabolic and fertility parameters. Patients and methods: This clinical trial, which was randomized, single-blind, and actively controlled, took place in Diwaniyah, Iraq, from October 2024 to June 2025. Participants were randomly assigned to three different groups. The random assignment was carried out using computer-generated random numbers. Patients in Group Met. received Glucophage (500 mg; Merck, West Drayton, UK) three times per day; Group Met.+ALA patients were given metformin as in the first group along with ALA (600 mg, Batch no. 6N5483; Holzkrichen, Bavaria, Germany) three times daily; Group Met.+ALA+CoQ10 patients received metformin and ALA as in the second group, along with 200 mg of CoQ10 each day. All treatments were provided over a duration of 12 weeks. Result: Post-treatment, all three forms of management showed significant decline in average free Testosterone, LH and LH:FSH ratio, GnRH anti-body and ovarian volume (p < 0.001); the effect of Met. plus ALA plus CoQ10 was significantly more profound when contrasted to other 2 modes of therapy (p < 0.05). However, none of these treatment approaches was able to affect serum levels of FSH, prolactin and TSH significantly (p > 0.05).Conclusion: The combined use of metformin therapy, CoQ10 supplements and ALA supplements is associated with the most optimum hormonal and ultrasound characteristic in PCOS women by reducing the pathogenic effect of anti GnRHR antibody level. Highlights: Combined Metformin, ALA, and CoQ10 improved hormonal and ultrasound parameters in PCOS. Significant reductions were observed in LH, free testosterone, LH:FSH ratio, and ovarian volume. No significant changes were found in FSH, prolactin, or TSH levels. Keywords: Polycystic Ovary Syndrome, Metformin, Alpha Lipoic Acid, Co-Enzyme Q10